Growth, yield, and oil content of Brassica species under Brazilian tropical conditions - Bassegio, Doglas [UNESP]; Zanotto, Mauricio Dutra [UNESP] (Inst Agronomico, 2020)
Brassica oilseed species are becoming increasingly popular for industrial uses, with emphasis on biodiesel. It is of importance to evaluate the yield and oil production potential of nontraditional oilseeds for use as feedstock in Brazil. In this study, growth, yield, and oil content and their correlations were determined for eight accessions of B. juncea and B. rapa in two years under tropical conditions of southeastern Brazil. Significant variation was observed between B. juncea and B. rapa accessions for yield components and oil content. B. rapa was the earliest maturing and had the highest oil content, whereas B. juncea had the highest number of pods and the highest yield and oil yield. Brassica rapa accessions flowered early, with an average cycle of 97 days, whereas B. juncea reached maturation after 110 days on average. Accessions were grouped according to the oil content of each species, with the most promising accessions having an oil content of 45-47%. Accessions of Brassica species had high oil yields, reaching 910 kg ha(-1) of oil yield for B. juncea PI 180266. There was a linear correlation between oil content and thousand seed weight, pod length, and seeds per pod of the Brassica species accessions. Considering oil content and oil yield across years, Brassica species show promise asalternative oilseed crops for biodiesel production in tropical conditions.
Keywords: vegetable oils; biodiesel; Brassica; germplasm